2019
DOI: 10.1039/c9cp02798j
|View full text |Cite
|
Sign up to set email alerts
|

Neural network potential energy surface and dynamical isotope effects for the N+(3P) + H2 → NH+ + H reaction

Abstract: Dynamical isotope effects are calculated for the N+(3P) + H2 → NH+ + H reaction on a new neural network potential energy surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…The three-body term was fitted with about 10 200 MRCI points to an rmse of 0.095 kcal/mol (33 cm –1 ) and used in quasiclassical trajectory studies. The three-body term of the PES for the N + ( 3 P) + H 2 → NH + + H reaction was fitted with the PIP-NN method in ref and time-dependent wave packet calculations were performed of the rovibrational state distributions and state resolved angle distributions of the product and of the isotopic effect on them. The PES was fitted to about 30 000 MRCI points to an rmse of 2.7 meV (22 cm –1 ).…”
Section: Applications Of Neural Network To Build Potential Energy Sur...mentioning
confidence: 99%
See 1 more Smart Citation
“…The three-body term was fitted with about 10 200 MRCI points to an rmse of 0.095 kcal/mol (33 cm –1 ) and used in quasiclassical trajectory studies. The three-body term of the PES for the N + ( 3 P) + H 2 → NH + + H reaction was fitted with the PIP-NN method in ref and time-dependent wave packet calculations were performed of the rovibrational state distributions and state resolved angle distributions of the product and of the isotopic effect on them. The PES was fitted to about 30 000 MRCI points to an rmse of 2.7 meV (22 cm –1 ).…”
Section: Applications Of Neural Network To Build Potential Energy Sur...mentioning
confidence: 99%
“…Even if they converge to the desired accuracy, they may require astronomic and unnecessary numbers of epochs; NN fits with tens of thousands of epochs with the Adam optimizer have been reported. 324 W e 6 9 , 1 0 1 , 1 1 5 , 1 1 7 , 1 1 8 , 1 4 2 , 1 6 5 , 1 6 6 , 1 6 8 , 1 8 0 , 2 1 9 a n d others 143,145,147,148,160,161,170,171,189,197,206,224,261,266,271,325 found that it is necessary to use the Levenberg−Marquardt (LM) algorithm. 196 While the cost per epoch is higher with Hessian-based algorithms, the convergence is much better and the overall cost lower.…”
Section: Notes On Software Implementationmentioning
confidence: 99%
“…48,146 Practically, the required PIPs under the order of M can be obtained by the software, MAGMA 147 and SINGULAR. 148 Full-dimensional accurate PESs of the following systems have been fitted by the PIP-NN method: F + HCl, 149 H + Li2 → Li + LiH, 150 Si + H2 → SiH + H, 151 N + O2 (doublet, quartet, and sextet states), 152 H + MgH → Mg+H2, 153 O + + H2, 154 S + + H2 → SH + + H, 155 K + H2 → H + KH, 156 H + HBr → H2 + Br, 157 N + + H2 → NH + + H, 158 Au + + H2 → H + AuH + , 159 OH + SO → H + SO2, 102,103 C + H2O → CO + H2/2H, 160 F + H2O → HF + OH, 94,126,161 Cl + H2O → HCl + OH, 84 HCl + OH → Cl + H2O, 162 OH + CO → H + CO2, 163 HOCO -, 164 CO + CO, 132 O + H2O, 126,165 H + HO2, 166 C2H2, 167 HF + HF, 168 KRb + KRb → K2 + Rb2, 169 H + H2S → H2 + SH, 170 NH + + H2 → N + H3 + /NH2 + + H, 171 OH + O2 → H + O3/ HO2 + O, 88 OH + + H2 → H + H2O + , 172 H2 + HF, 173 NH3, 174 H2 + HCl, 124 N2 + HF, 175 N2 + HOC + → N2H + + CO/N2 + HCO, 176 CH2OO, 114 dioxirane, 117 O + C2H2 → H + HCCO/CO + CH2, 177 CO + H2O, 123 C2H2 + Ne, 178,179 OH + H2O → H2O + OH, ...…”
Section: Data Fitting 41 Pip-nnmentioning
confidence: 99%
“…For example, it usually takes tens of thousands of points to build complex-forming reactive PESs dominated by a well even for the simplest triatomic systems. [10][11][12] Therefore, it is a key issue to efficiently sample data points in the nuclear configuration space to make the construction of polyatomic or complex structured PESs truly possible.…”
Section: Introductionmentioning
confidence: 99%